Odpowiedzi

2010-03-23T19:45:39+01:00
A) 2y-ab=c
2y=c+ab /:2
y=c+2b/2
b) b=-ay + dv
ay=dv-b /:a
y=dv-b /a
c) ay-c=4ay-d
ay-4ay=c-d
-3ay=c-d /:-3a
y=c-d/-3a
d) 3by –z –a=2by
3by-2by=z+a
by=z+a /:b
y=z+a /b
2010-03-23T19:47:17+01:00
A) 2y-ab = c
2y = c+ab
y = (c+ab)/2

b) b=-ay + dv
ay = dv - b
y = (dv - b)/a

c) ay-c=4ay-d
ay - 4ay = c-d
-3ay=c-d
y = (c-d)/(-3a)

d) 3by –z –a=2by
3by – 2by = z + a
by = z+a
y = (z+a)/b
2010-03-23T19:48:09+01:00
A) 2y-ab=c
2y = c + ab
y = (c + ab)/2
b) b=-ay + dv
ay = dv - b
y = (dv - b)/a
c) ay-c=4ay-d
ay - 4ay = c - d
y(a - 4a) = c - d
y = (c - d)/-3a = - (c - d)/3a = (d - c)/3a
d) 3by –z –a=2by
3by - 2by = a + z
by = a + z
y = (a + z)/b